READING X, Y COORDINATES WITH OPTICAL MOUSE AND SENDING DATA VIA INTERNET WITH NODEMCU-ESP8266 - TODICA, M. (Studia Universitatis Babeș-Bolyai Physica, 2018)
The work demonstrates the possibility to read the x, y coordinates of a moving object using an optical PC mouse and send the data to Android devices (smartphone or tablet) using the NodeMcu-ESP 8266 board. The system was used to control a small robot car with a smartphone via internet. The method can be usefully for didactic and scientific experiments.